Benefits of Rice-Beef Cattle Integration System Farming Based on Increasing Income of Rice Farmers on Tongauna North District, Konawe Regency - Cahyani, Dewi Nurul; Limi, Muhammad Aswar; Fyka, Samsul Alam (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This study aims to determine the benefits of implementing the rice-beef cattle integration system at the household scale in the North Tongauna District, Konawe Regency. This research was conducted in September-October 2021. The determination of the sample in this study used the Slovin Method, which continued using the proportional random sampling technique so that the number of respondents was 43 farmers. Data analysis determines the benefits obtained through income and benefit-cost ratio (BCR) analysis. The results showed that the benefits received by lowland rice farmers through the application of the integrated system of lowland rice - beef cattle, namely in the form of additional benefits from the sale of livestock cattle, amounting to IDR9.162.791/year so that the total benefit obtained by lowland rice farmers is IDR49.278.512/year. So that the net benefits obtained by lowland rice farmers from this integrated system after deducting production costs are IDR41.047.139/year. While the BCR value obtained from the integrated system of rice cattle - beef cattle is 4.98.